Implementation of learning models by high school teachers in the time of covid-19 with the school of students in the City of Lhokseumawe - Ahyar, Juni; Edyansyah, T. (Universitas Malikussaleh, 2021)
The learning model is a conceptual framework that is used as a guide in carrying out learning activities. With the use of models, learning can be more directed, easy to understand, and mastered by students. Hence, the use of models in learning must be in accordance with the theory being taught, the goals to be achieved, and the environment and students must also be considered. In addition, the model used must also be fully controlled by the teacher. If these factors are not considered, the final result will not be as expected. Problems arise, students do not want to learn, the learning atmosphere is uncomfortable, the teacher is also uncomfortable in teaching, so that the students' grades are not optimal. Therefore, in this study, Researchers want to see how the model is applied by teachers, especially Indonesian language subject teachers, as well as the Covid-19 period with student final grades (UNAS). The method used in this research is qualitative method. Researchers will describe the final results of the study, then draw a conclusion. In collecting data, researchers used observation, interview, and documentation study techniques. Observations here, are not only observations in the classroom, but also researchers make observations of other facilities and infrastructure. Through this research, it is hoped that (1) there will be an image as a reference material for related agencies in making policies to improve the quality of education, (2) a reference for other educators on the application of an effective model, and (3) find the latest learning models that might be found in this study. Then, the results of this research are also targeted to be published in national seminars and journals.